Cadmium stress alleviation potential of Bruguiera cylindrica (L.) Blume enhances in combination with NaCl. Issue 2 (3rd April 2022) - Sruthi, Palliyath; Puthur, Jos T.
Abstract: A hydroponic experiment in NaCl tolerant mangrove, Bruguiera cylindrica plantlets was done to investigate the interactive effects of CdCl2 +NaCl as well as the individual effects of CdCl2 . CdCl2 alone results in enhanced level of cell membrane lipid peroxidation, damaging normal structure, and function of the membrane and there by leading to reduction of membrane stability index and thus severely promoting the electrolyte leakage than the combined treatment of CdCl2 +NaCl. Antioxidants greatly contribute to cope with the stress by scavenging ROS and were more prominent in individual stress than combined stress. B. cylindrica can be categorized as a highly tolerant mangrove species with a Tolerance Index (TI) of above 60% toward CdCl2 +NaCl (TI is 70 and 75% in leaf and root). But TI was only 63 and 67% in leaf and root, respectively, on exposure to CdCl2 alone indicating that this plant is less tolerant to Cd alone. The existence of B. cylindrica depends on the heavy metals being introduced into the mangrove ecosystem and imparts a combination stress along with NaCl. In this regard, B. cylindrica survives up to 0.20 mM CdCl2 along with NaCl. Thus, the high NaCl tolerance mechanisms in this mangrove species could be equally efficient in imparting tolerance toward high concentration of Cd along with NaCl and exhibits phytostabilization in polluted coastal wetlands.